Implementation of the Arabic Debate Method in Teaching Speech Skills: تنفيذ طريقة المناظرة العربية في تعليم مهارة الكلام - Ita Nur Istiqomah; Muhammad Nidom Hamami Abicandra (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2021)
This research aims to describe the implementation of the Arabic debate method used in the Arabic Language Education Division and the use of the Arabic debate method to upgrade speaking skills in the Arabic Language Teaching Division. This research uses the qualitative approach and its descriptive type and the choice of this approach to describe the use of the Arabic debate method to upgrade the skill of speech in the Arabic Language Teaching Division at the State Islamic of Jember. It has been evident through this research that: a) The Arabic debate method used in the Division of Arabic Language Education at the Islamic State Islamic of Jember means (1) Debating is the preferred method in the Division of Arabic Language Education to sharpen these students the understanding of logical thinking, (2) Debate is how they practice All students to speak Arabic, think seriously, use rhetoric, and make students discipline and responsibility in their roles, (3) Debating stirred the enthusiasm of all students in Arabic speech. Third, if you find a great environment in the debate subject learning, you do not feel bored when studying them; this is a lovely thing in the debate course in the Department of Teaching Arabic Language.